Grieving for Job Loss and Its Relation to the Employability of Older Jobseekers - Climent-Rodríguez, José Antonio; Navarro-Abal, Yolanda; López-López, María José; Gómez-Salgado, Juan; García, Marta Evelia Aparicio (Frontiers in Psychology, 2019)
Introduction: Loss of employment is an experience that is lived and interpreted differently depending on a series of individual variables, including the psychological resources available to the affected person, as well as their perception of their degree of employability. Losing one’s job can be one of the most painful and traumatic events a person has to withstand. Following a dismissal, the worker needs to overcome a period of emotional adaptation to the loss. But that period of grieving can also condition the process of job search of the person, and be influenced by different variables, highlighting the age and work experience. The objective of this study is to analyze the relationship between intensity and type of affliction due to the loss of employment in older workers and their level of employability. Method: We carried out a descriptive, analytical, cross-sectional study. The sample consisted of 140 unemployed participants, from 19 to 65 years of age, users of job Orientation in the Public Employment Service of Andalusia (España). Of the total participants, 66 were unemployed and over 45 years of age. They all took the Labour Insertion Potential Assessment Test, and the Texas Inventory revised adapted to job loss Results: Significant differences are shown in the grieving process due to loss of employment between both groups, with the older unemployed living the process more intensely. In relation to the employability potential, differences are found between both groups in terms of availability, perceived difficulties and fears. Interrelationships between total grieving intensity and the importance that older jobseekers give to work are also indicated. Conclusion:Loss of employment and the psychological and health consequences of this situation are identified with those that arise in the grieving process. Older workers present a series of features that determine that their job loss grieving process is more intense and lasts longer than that of other younger workers, regardless of whether the job loss was recent or not. On the other hand, it is shown that the intensity of grieving is related to the decrease of certain variables that are part of the concept of employability.